Reflective Teaching Approach: Theory And Practice For Effective Arabic Learning/ Pendekatan Reflective Teaching: Teori Dan Praktik Untuk Pembelajaran Bahasa Arab Yang Efektif - Faiq Ilham Rosyadi; Hisyam Zaini; Nasiruddin Nasiruddin (Ijaz Arabi Journal of Arabic Learning, 2022)
The approach to learning Arabic often applied is only limited to a specific focus. This causes the quality of learning Arabic not to reach its maximum rate. This study aims to formulate the Arabic language learning approach framework through reflective thinking. This article is from a literature study using the descriptive analysis method. The data collection technique used in this research is through exploration and in-depth study of documents, books, journal articles, or other text sources related to the research subject. The primary data of this research is the educational framework "OECD Future of Education and Skills 2030 Conceptual learning framework-Anticipation-Action-Reflection Cycle for 2030". After collecting the data needed in the study, the data is reviewed, analyzed, interpreted, and packaged into a comprehensive learning approach framework. The results of this study indicate that the reflective approach guides the teacher's awareness in exploring, questioning, and reframing the portrait of learning that has been done to make interpretations and make appropriate and sustainable choices. The reflective approach to learning Arabic can be made through three stages of questions. First, questions about what happens in the classroom, questions for yourself as a teacher, and questions about teaching done by teachers. Meanwhile, practically, the reflective teaching approach can be realized in the following steps: mapping, informing, contesting, appraisal, and acting. Mapping deals with the question "as Arabic teachers, what should we do? Informing relates to the question "what is the nature of teaching?" Contesting relates to the question "how should we teach?" Appraisal relates to a question "How do Arabic teachers teach with new alternatives?" Acting is related to the teacher's understanding of new alternatives to teaching.